Esthétique de la peur et de la cruauté chez deux nouvellistes francophones contemporaines : Marie José Thériault et Nadine Monfils - Vauthier, Éric (Romanica Silesiana)
Marie José Thériault (1945), from Quebec, and Nadine Monfils (1953), from Belgium, began their narrative writing career almost at the same time – the first one in 1978, with La Cérémonie, and the second one in 1981, with Laura Colombe, contes pour petites filles perverses. In their tales, they both show a predilection for the fantastic as well as for the marvelous, and they explore dark inspiration which can arouse anguish, fear or even horror. They both express this inspiration through real aesthetics of cruelty, and by expanding an inner world in which morbid eroticism figures prominently. These are some aspects studied in this paper. Key words: short story, cruelty, eroticism, Francophone literature